Associations between alcohol use and outcome of psychological treatment in specialist psychiatric care – a cohort study - Lundkvist, Jan Erik; Georgsson, Katarina; Carlbring, Per; Johansson, Robert; Ljungberg, Tomas; Wallhed Finn, Sara; Anderbro, Therese (Frontiers in Psychology, 2024)
Background Alcohol-related issues are widespread worldwide and are fairly substantial. Numerous studies have identified and clarified the effects and prevalence of alcohol use across different contexts. However, when it comes to the prevalence of alcohol in psychiatry and its impact on treatment outcomes compared to other patient groups, studies are relatively scarce, and results often vary, sometimes with different outcomes. This study focuses on investigating the effectiveness of psychological treatment in psychiatric clinics for outpatients, considering those with and without hazardous alcohol use under naturalistic conditions. Methods Patients were recruited between 2012 and 2016 from psychiatric clinics in Sormland, Sweden, as part of the regular services. Patients completed symptom assessment instruments regarding depression, anxiety, quality-of-life, and alcohol consumption at the beginning of their psychological treatment, upon completion, and during a follow-up 1 year after completion. Completion of questionnaires was ongoing for some patients until 2021. A total of 324 patients were included in the study, distributed among 59 participating therapists. Results Among all patients in the study, 30.2% showed hazardous alcohol use at the start of their psychological treatment, with a higher proportion being men. There was a significant reduction in the proportion of patients with hazardous use and a notable decrease in the mean audit score upon completion of psychological treatment. At follow-up, there was no significant change compared to completion. There were 31.2% of the patients who achieved recovery or improvement in the audit score upon completion of treatment. Patients with hazardous alcohol use consistently scored higher mean values on the symptom assessment instruments and lower on the quality-of-life instrument at the beginning. More individuals with hazardous alcohol use typically achieved better results across all outcome instruments at both at completion and follow-up. Conclusion Patients with hazardous alcohol use demonstrate significant improvements in their alcohol consumption through standard psychological treatment in psychiatry, despite the treatment not specifically focusing on alcohol consumption. The progress/improvement appears to be largely maintained at follow-up. Moreover, patients with hazardous alcohol use tend to show greater progress across all outcome instruments. No significant gender differences were detected in this context.